Răspunsuri

2014-09-22T22:23:16+03:00
A) 4(2x+3)-15=2x
8x+12-15=2x
8x-2x=15-12
6x=3
x=3/6 simplificam=1/2
b) 6(3x+5)-6=3x
18x+30-6=3x
18x-3x=6-30
15x=-24
x=-24/15 simplificam cu 3=-8/5
c) 6(x+2)-4x=8
6x+12-4x=8
2x=8-12
x=-4/2=-2
d)7(x-6)-2x=9
7x-42-2x=9
5x=9+42
x=51/5
e) 8(x+3)-4x=10
8x+24-4x=10
4x=10-24
x=-14/4 simplificam=-7/2
2014-09-22T22:32:43+03:00
A) 8x + 12 - 15 = 2x
8x - 2x = 15 - 12
6x = 3
x = 3/6
 x = 1/2
b) 18x + 30 - 6 = 3x
18x - 3x = - 30 + 6
15x = - 24
x = - 24/15
x = - 8/5
x = - 1 si 3/5
c) 6x + 12 - 4x = 8
2x = 8 - 12
x = - 4/ 2
x = - 2
d) 7x - 42 - 2x = 9
5x = 42 + 9
x = 51/5
x = 10 si 1/5
e)8x + 24 - 4x = 10
4x = - 24 + 10
4x = - 14
x = - 14/4
x = - 7/2
x = - 3 si 1/2